Enhancing recruitment and retention strategies in human tobacco research - Laraib Mazhar; Nicolle Krebs; Sophia I. Allen; Andrea L. Hobkirk; Matthew Carrillo; Craig Livelsberger; Vicki Peters; Jonathan Foulds; Jessica M. Yingst (PLoS ONE, 2026)
Introduction Recruitment and retention of study participants in tobacco research studies is challenging, and many studies are not able to meet desired sample sizes, particularly since the COVID-19 pandemic. This survey study explored tobacco users’ motivations and expectations when considering participation in tobacco research and identifies common barriers to participation. Methods Participants were adult (21+) tobacco users recruited from a registry of potential research participants. In 2023, participants were emailed a survey to ascertain their motivations for participating in tobacco and health research, their expectations for participation, including compensation and barriers to participating. Means, medians, and proportions were calculated to describe the study population and outcomes. A binary variable for compensation importance was created and analyzed using logistic regression adjusting for demographic and tobacco use factors. Results Participants (n = 267) had a mean age of 46.9 years (SD 11.47) and were 67.4% female, 91.0% White, and 3.4% Hispanic. The majority smoked cigarettes (84.3%), while 34.5% reported electronic cigarette use. Most participants (79.4%) indicated interest in tobacco research because they wanted to quit or reduce smoking/tobacco use. Anticipated median compensation for completing a visit lasting one hour with questionnaires was $25, or $50 if a blood draw was included. Two-thirds (66.7%, n = 178) of participants viewed compensation as important. Younger age was associated with the perceived importance of higher compensation (OR=0.971, 95% CI: 0.949–0.993, p = 0.011). The most commonly reported barriers to participation were related to current work schedule issues (41.6%) and not having the ability to take off work when the research center was open (38.6%). Conclusion Most participants were interested in tobacco and health research for the intrinsic benefit of quitting or reducing smoking. Removing scheduling and transportation issues with remote research when possible, may increase participation rates. When intrinsic benefit is not available, appropriate compensation should be utilized to boost recruitment and retention rates.